Conceptualizing soil fauna effects on labile and stabilized soil organic matter - Angst, Gerrit; Potapov, Anton; Joly, François-Xavier; Angst, Šárka; Frouz, Jan; Ganault, Pierre; Eisenhauer, Nico (Nature communications, 2024)
Fauna is highly abundant and diverse in soils worldwide, but surprisingly little is known about how it affects soil organic matter stabilization. Here, we review how the ecological strategies of a multitude of soil faunal taxa can affect the formation and persistence of labile (particulate organic matter, POM) and stabilized soil organic matter (mineral-associated organic matter, MAOM). We propose three major mechanisms - transformation, translocation, and grazing on microorganisms - by which soil fauna alters factors deemed essential in the formation of POM and MAOM, including the quantity and decomposability of organic matter, soil mineralogy, and the abundance, location, and composition of the microbial community. Determining the relevance of these mechanisms to POM and MAOM formation in cross-disciplinary studies that cover individual taxa and more complex faunal communities, and employ physical fractionation, isotopic, and microbiological approaches is essential to advance concepts, models, and policies focused on soil organic matter and effectively manage soils as carbon sinks, nutrient stores, and providers of food.
Keywords: mikrobiota; Minerals; uhlík; ekosystém; půdní mikrobiologie; minerály; Animals; organické látky; půda; Soil Microbiology; Microbiota; Ecosystem; zvířata; Carbon; Organic Chemicals; Soil